Increasing protectivity of the smallpox vaccine - S. N. Shchelkunov; A. A. Sergeev; K. A. Titova; S. A. Pyankov; S. N. Yakubitskiy (Медицинская иммунология, 2022)
At the present time, vast majority of human population lacks immunity against orthopoxvirus infections caused by variola (smallpox), monkeypox, cowpox, or buffalopox viruses. More and more mass outbreaks of orthopoxvirus infections are yearly registered among humans on different continents. To prevent transition of these outbreaks to widespread epidemics, we should develop appropriate immunoprophylaxis strategies. Currently, massive usage of the classic live vaccine based on vaccinia virus is not acceptable, due to its high reactogenicity. Therefore, it is necessary to develop the variants of vaccinia virus with reduced virulence and increased immunogenicity/protectivity. The aim of this work was to study protective effects against a lethal orthopoxvirus infection occuring after low-dose immunization of mice with vaccinia virus variants, i.e., carrying mutant A34R gene causing increased production of extracellular virions, or a A35R gene deletion encoding protein product inhibiting antigen presentation by the major histocompatibility complex class II. The LIVP viral strain used in Russia as a smallpox vaccine, and its recombinant variants (LIVP-A34R*, LIVP-dA35R and LIVP-A34R*-dA35R) were compared with intranasal or intradermal immunization of BALB/c mice at the doses of 105 or 103 PFU. 28 days following administration of viral preparations (experimental groups) or saline (control groups), the mice underwent intravital blood sampling from retroorbital venous sinus. The levels of virion-specific antibodies were determined in individual serum samples by enzyme immunoassay. On the day 30 of experiment, the mice were infected with cowpox virus at a dose of 32 LD50, which caused total death of control mice on days 6-10. In the groups immunized with the studied viruses at a dose of 105 PFU, all the animals survived, regardless of strain, or immunization method. Upon intradermal immunization (103 PFU) of mice immunized with the original LIVP virus, 83% of the animals survived, whereas all mutant strains of the vaccinia virus provided 100% protection of the mice from subsequent cowpox virus infection. Intranasal immunization of mice at a dose of 103 PFU with LIVP strain protected only 33% of animals from lethal infection with cowpox virus, while the mutant strains LIVP-A34R* and LIVP-A34R*-dA35R provided 67% protection, and the LIVP-dA35R strain has resqued 75% of the mice. The studied mutant vaccinia viruses can be considered not only new candidate vaccines against smallpox and other human orthopoxvirus infections, but also as vector platforms for creating live multivalent vaccines against other infectious diseases.